Dog breed guide : the complete reference to your best friend fur-ever - Resler, Tamara J.; Weitzman, Gary (Washington, D.C. : National Geographic, 2019)
From dachshunds to Dalmatians and poodles to pugs, this comprehensive guide gives an overview of more than 400 different dog breeds. Each profile includes the breed's "dog stats": country of origin, size, coat color and pattern, grooming difficulty, exercise needs, and "K-9 qualities." With the help of veterinarian Dr. Gary Weitzman and dog behaviorist Amanda Kowalski, kids will also learn how to choose the right dog for them, how to take care of their new furry friend, and how to understand their behavior. Fantastic feature spreads cover dogs in popular culture, dog ancestry, how to prepare for your perfect pooch, dogs with jobs, and so much more. This comprehensive guide is perfect for dog-loving kids, and an excellent reference for families who are who are bringing home their first four-legged family member.
What is a dog? -- Dog breed guide -- Picking a pup.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references (page 280) and index.
Description based on print version record.
Keywords: Dogs -- Juvenile literature; Dog breeds -- Juvenile literature; Dogs; Dog breeds; JUVENILE NONFICTION / Animals / Dogs; JUVENILE NONFICTION / Animals / Pets; JUVENILE NONFICTION / Reference / General; Dogs -- Juvenile literature; Dog breeds -- Juvenile literature; Dog breeds; Dogs; Electronic books- OSLIS; Illustrated works; Juvenile works; Illustrated works; Electronic books